KETERSEDIAAN TANAH BAGI MASYARAKAT RAWAN BENCANA - Westi Utami (BHUMI: Jurnal Agraria dan Pertanahan, 2014)
The high threat of disaster / multi-disaster in Indonesia leads to a number of communities in a state of being exposedand vulnerable to disasters. The high number of people living around the source of disaster / KRB III also causes the high degreeof potential risk and loss if the disaster occurs. The National Land Agency has pivotal role in regulating land for development, in thiscase, through the provision and arrangement of land for settlement (relocation) and for infrastructural development for the peopleliving in the disaster-risk areas. This study employed review of literature and legal products on land availability as its method andapproach. The allocation of land, particularly for the people living in disaster-risk areas, may be provided through land acquisition,land utilization of reserved State land from previously abandoned land, or may also be provided through land consolidation basedon spatial planning.This is intended to achieve the quality of environment, safe and prosperous society.Keywords: land availability, land consolidation, disaster